Developing the Gross Motor Skills of Children by Simultaneously Training Them with Rhythmic Gymnastics - Arifin Manggau; Arifudin Usman (Universitas Negeri Makassar, 2020)
The purposes of this study were (1) to describe the gross motor skills of children before and after being trained with rhythmic gymnastics, and (2) to identify the effect of rhythmic gymnastics on children’s gross motor skills. Approaches applied in this study were pre-experimental with one-group pretest - post-test design. The study involved 15 children from the B group of Pertiwi Kindergarten selected through a purposive sampling technique. The data were collected using a questionnaire, observation, and documentation. The research was carried out through some stages including planning, pretest, treatment, post - test, and data analysis. Data were analyzed using the Wilcoxon Signed Rank Test. This study found that (1) children’s gross motor skills before trained with rhythmic gymnastics were in the categories of “not developed” and “starts to develop” and after the treatment, there was an increase on children’s gross motor skills thus the status shifted to the category of “developed as expected” and “developed very well” in performing locomotor, non-locomotor, balance, and flexibility movements like children could walk forward while both hands were on their waist, jump in place while swinging both arms, balancing the body by lifting one of the legs, and swing the arms back and forth alternately; (2) rhythmic gymnastics have effects on children’s gross motor skills, simultaneously treating children with rhythmic gymnastics with various interesting movements so that they become interested to follow them thus it is effective to be a media to form children’s gross motor skills simultaneously.